2011
DOI: 10.1038/mt.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Therapeutic pRNA-siRNA Nanoparticles Using Bipartite Approach

Abstract: The 117-nucleotide (nt) RNA, called the packaging RNA (pRNA) of bacteriophage phi29 DNA packaging motor, has been shown to be an efficient vector for the construction of RNA nanoparticles for the delivery of small interfering RNA (siRNA) into specific cancer or viral-infected cells. Currently, chemical synthesis of 117-nt RNA is not feasible commercially. In addition, labeling at specific locations on pRNA requires the understanding of its modular organization. Here, we report multiple approaches for the const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…Following standard pRNA nomenclature (Shu et al 2011b), the right-hand (R-loop) sequence was assigned an uppercase letter (i.e., A, B, …); the left-hand (L-loop) sequence, a lowercase letter with a prime (i.e., a ′ , b ′ , …). A pair of the same uppercase and lowercase letters (e.g., Aa ′ ) designated a complementary sequence in the R/L interlocking loop, while different letters indicate a lack of complementarity in the interlocking sequence.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Following standard pRNA nomenclature (Shu et al 2011b), the right-hand (R-loop) sequence was assigned an uppercase letter (i.e., A, B, …); the left-hand (L-loop) sequence, a lowercase letter with a prime (i.e., a ′ , b ′ , …). A pair of the same uppercase and lowercase letters (e.g., Aa ′ ) designated a complementary sequence in the R/L interlocking loop, while different letters indicate a lack of complementarity in the interlocking sequence.…”
Section: Nomenclaturementioning
confidence: 99%
“…A dual-luciferase reporter assay system was used to measure the gene silencing effects of pRNA tetrameric constructs harboring four different siRNAs targeted toward the firefly luciferase gene (Shu et al 2011b). The relative luciferase activity is proportional to the expression level of the firefly luciferase gene when normalized with the activity of the internal control, Renilla luciferase, which remains unaffected against siRNA.…”
Section: Targeted Gene Silencing Of Luciferasementioning
confidence: 99%
“…1A-C, 2B-C, 3) (Shu et al, 2004). In the succeeding years, through a series of papers, they showed that pRNA molecules could be conjugated with various therapeutic functionalities including aptamers, small interfering RNA (siRNA), ribozymes, and microRNA (miRNA) Guo et al, 2005;Khaled et al, 2005;Guo et al, 2006;Shu et al, 2009;Abdelmawla et al, 2011;Ye et al, 2011;Shu et al, 2011a;Shu et al, 2011b;Shu et al, 2011c;Zhang et al, 2009) 4). These findings have paved the way for RNA nanotechnology to develop into a novel area of therapeutics for the treatment of various diseases such as cancer, viral infections, and genetic diseases.…”
Section: Historical Evolution Of Rna Nanotechnologymentioning
confidence: 99%
“…The production of oligonucleotides with functional moieties then becomes a scalable process (chemically) and with a modular design the complex can be self-assembled from the basic building blocks. Using this methodology, thermodynamically and chemically stable pRNA-based nanoparticles with functional modules were successfully fabricated using a bipartite, tripartite, and tetrapartite approach with various modifications (Shu et al, 2011a;Shu et al, 2011b).…”
Section: Low Yield and High Production Costsmentioning
confidence: 99%
See 1 more Smart Citation